Obstacles to the use of e-learning at Al-Mustansiriya University from the point of view of faculty members (Journal of the College of Basic Education, 2024)
The current research aims to identify the obstacles to the use of e-learning at Al-Mustansiriya University from the point of view of the faculty members. The current research is limited to the faculty members at Al-Mustansiriya University, where a random sample of (100) male and female teachers from Al-Mustansiriya University was selected. To achieve the research objectives, the researcher By preparing a scale to measure the obstacles to the use of e-learning at Al-Mustansiriya University from the point of view of faculty members, the researcher arrived at a set of results, and according to these results, the researcher came out with conclusions, recommendations, and proposals